Gambaran kebiasaan belajar siswa serta Implikasi nya terhadap Pelayanan Bimbingan dan Konseling - Solihatun Solihatun (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
This study aimed to find out the description of students' learning habits in Depok Master High School Indonesia. This research uses descriptive method with a quantitative approach. The population of this study includes all students of class X, XI and XII of Depok Master High School who are enrolled in the 2017-2018 school year as many as 105 students who become research subjects using saturated sampling technique is a sampling technique if all populations are used as samples. Furthermore, to find out the study habits researchers used quantitative methods with a descriptive approach. The instrument uses a Likert scale. The results showed that the study habits of students in SMA Master Indonesia Depok were in the good category that is equal to 54.29% (57 people), good enough category 36.19% (38 people), excellent category 5.71% (6 people ), 3.81% unfavorable category (4 people). The implications of the research results can be used as an analysis of students' needs for the provision of BK services in maintaining student learning habits.